MORTALITY ANALYSIS OF THE PATIENTS WITH ALCOHOLIC LIVER CIRRHOSIS - Matkovska, N. R. (International Journal of Medicine and Medical Research, 2019)
Background. Alcohol is considered to be the main risk factor for adverse event deaths around the world. In Ukraine, mortality due to alcoholic liver disease (ALD) has taken the second place in the structure of death causes from diseases of the digestive system. Objective. The aim of the research was to study the peculiarities of the causes of death in the patients with alcoholic liver disease at the stage of liver cirrhosis (LC) based on the analysis of protocols of pathoanatomical research. Methods. The analysis of 149 protocols of the pathoanatomical study of the patients, who died from alcoholic LC, has been carried out at the premises of the Pathoanatomical Department of the Ivano-Frankivsk Regional Clinical Hospital in 2006-2018. Results. Most people were young and middle aged. Fatal cases were caused by decompensation of the LC with the development of hepatic, hepatic-renal, cardio-pulmonary insufficiency, pancreatic necrosis, gastrointestinal bleeding (GIB), sepsis, hepatocellular carcinoma (HCC). In 37.6 % of the patients the concomitant illness was coronary heart disease (CHD), 10.7 % of the people had hypertension. In 6 % of the patients, ischemic stroke of the brain was diagnosed. In most people atherosclerotic vascular changes were revealed. Conclusions. Excessive consumption of alcohol and, consequently, the development of LC, can be considered as an adverse factor in the reducing social standard of living. In the majority of people, who died from the decompensation of alcoholic LC, atherosclerotic vascular lesions have been detected. This indicates a significant prevalence of lipid metabolism disturbance in the people with alcoholic LC.